Influence of a Green Environmental Orientation on Corporate Sustainable Performance in the Manufacturing Sector - Jian Chen; Nuttawut Rojniruttikul (My University, 2025)
As sustainability becomes a strategic imperative in the manufacturing sector, firms are increasingly adopting green environmental practices to enhance their competitive advantage and long-term viability. This study investigates the influence of an Internal (IGEO) or External Green Environmental Orientation (EGEO) on the Green Competitive Advantage (GCA), Green Innovation (GI), and Sustainable Performance (SP). Specifically, this research assesses the direct impact of an IGEO and EGEO on the GCA and GI, as well as their mediating roles in achieving sustainability objectives. To empirically validate the proposed conceptual framework, this study employs structural equation modeling (SEM) using survey data collected from 468 manufacturing firms in China. The findings reveal that an IGEO and EGEO are significant drivers of a GCA and GI, both of which, in turn, positively influence Sustainable Performance. The results underscore the importance of aligning internal sustainability initiatives with external environmental expectations to achieve superior long-term sustainability outcomes. This study contributes to the literature on green management by offering empirical evidence of the mechanisms through which a green orientation fosters sustainability. The insights derived have practical implications for firms seeking to integrate their internal capabilities with external environmental demands to develop a comprehensive and effective sustainability strategy. These findings serve as a valuable resource for researchers and practitioners aiming to enhance green competitiveness and innovation in the manufacturing sector.
Keywords: Green innovation; Manufacturing sector; Environmental Sustainability in Business